Misophonia: Analysis of the neuroanatomic patterns at the basis of psychiatric symptoms and changes of the orthosympathetic/ parasympathetic balance - Grossini, Elena; Stecco, Alessandro; Gramaglia, Carla; De Zanet, Daniel; Cantello, Roberto; Gori, Benedetta; Negroni, Davide; Azzolina, Danila; Ferrante, Daniela; Feggi, Alessandro; Carriero, Alessandro; Zeppegno, Patrizia (Frontiers in Neuroscience, 2022)
Background/Aim. Misophonia is a disorder characterized by reduced tolerance to specific sounds or stimuli known as “triggers”, which tend to evoke negative emotional, physiological and behavioral responses. In this study we aimed to better characterize participants with misophonia through the evaluation of the autonomic nervous system response to “trigger sounds”, a psychometric assessment, and the analysis of the neurological pathways. Materials and Methods. Participants included 11 adults presenting with misophonic disturbance and 44 sex-matched healthy controls (HCs). Following recently proposed diagnostic criteria, participants listened to six "trigger sounds" and a "general annoyance" sound (baby crying) during a series of physiological tests. The effects were examined through functional resonance magnetic imaging (fMRI), the analysis of heart rate variability (HRV), and of galvanic skin conductance (GSC). The fMRI was performed on a 3T Scanner. HRV was obtained through the analysis of electrocardiogram, whereas GSC was examined through the positioning of silver-chloride electrodes on fingers. Furthermore, psychometric assessment included questionnaires focused on misophonia, psychopathology, resilience, anger, and motivation. Results. Participants with misophonia showed patterns of increased sympathetic activation in response to trigger sounds and a general annoyance sound, the low frequency component of HRV, the sympathetic index, the number of significant GSC over the threshold, and the amplitude/phasic response of GSC were higher. The fMRI analysis evidenced the activation of the temporal cortex, limbic area, ventromedial prefrontal/premotor/cingulate cortex, and cerebellum in participants with misophonia. In addition, the psychometric assessment seemed to differentiate misophonia as a construct independent from general psychopathology. Conclusions. These results suggest the activation of a specific auditory-insula-limbic pathway at the basis of the sympathetic activation observed in participants with misophonia in response to “trigger and general annoyance sounds”. Further studies should disentangle the complex issue whether misophonia represents a new clinical disorder, or a non-pathological condition. These results could help to build diagnostic tests to recognize and better classify this disorder. The relevance of this question goes beyond purely theoretical issues, as in the first case, participants with misophonia should receive a diagnosis and a targeted treatment, while in the second case they should not.